Geology and genesis of Lago volcaniclastic-hosted Zn-Pb deposit, northwest Spain - D. Arias; L. Villa; L. G. Corretge; O. Suarez (The Institute of Materials, Minerals and Mining, 1905)
The deposit comprises two vertical, lenticular bodies emplaced in the allochthonous block of a Variscan thrust. Epigenetic mineralisation occurs as replacement of carbonated volcaniclastic rocks of Cambro-Ordovician age. The dominant sulphide minerals are sphalerite and galena with minor chalcopyrite; the main non-metallic mineral is quartz and there is hydrothermal silicification, chloritisation and sericitisation. Sulphur isotope values for sphalerite and galena are heavy and reflect the fundamental relationship between delta-34S in ZnS and in PbS, suggesting isotopic equilibrium. Four sphalerite-galena pairs yield temperatures between 163 and 218 degrees C, in good agreement with the 187-207 degrees C estimated by the Ga/Ge-sphalerite geothermometer. The ore sulphide was leached by the hydrothermal solution from diagenetic pyrite in the host rocks and disseminated sphalerite and galena in Cambrian carbonates